Influence of digestion time on the mechanical properties of gap graded hot mixes produced with asphalt rubber binders - Dantas Neto, Silvrano Adonias (2009)
Asphalt rubber binders are produced by mixing crumb rubber obtained from ground used tires with a straight run binder at high temperatures during a period of time named as digestion time. This is one of many variables that influence the physical properties of asphalt rubber produced by wet process. Thus, the objective of this paper is to evaluate how many mechanical properties of gap-graded hot mixes produced with asphalt rubber binder are influenced by the digestion time used to produce this modified binder. The asphalt rubber binders were produced by incorporating 21% in weight of crumb rubber into a straight run binder at 210 C. The digestion limes used were 60 and 300 minutes. These asphalt rubber binders were used to produce gap-graded hot mixes which were submitted to tensile strength, fatigue life, resilient modulus and permanent deformation tests. The results show that the increase of digestion time used to produce asphalt rubber binders led to a decrease of tensile strength, resilient modulus and permanent deformation However there was a significantly increase of fatigue life of asphalt hot mixes studied.